A CLINICAL PSYCHOLOGY EXAMINATION OF THE INTEGRATION OF ISLAMIC VALUES AND SOCIO-EMOTIONAL DEVELOPMENT IN EARLY CHILDHOOD - Solihin, Muhammad; Narti, Wiwin; Tania, Liza (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to examine the integration of Islamic values in the social-emotional development of early childhood. The main focus of the study is to analyze the effect of the application of Islamic values on social-emotional aspects, such as social interaction skills, emotional management, and character building in early childhood. The method used is a qualitative approach with case studies involving observation, interviews with parents and educators, and analysis of documents related to Islamic education in early childhood education institutions. The results of the study indicate that the application of Islamic values, such as compassion, honesty, patience, and responsibility, contribute significantly to improving children's social-emotional abilities, especially in forming positive behavior and harmonious relationships with peers. The implication of this study is the importance of integrating Islamic values in the early childhood education curriculum to support healthy and positive social-emotional development, as well as provide a strong foundation for children's moral and character development in the future.